PROSEDUR PEMERIKSAAN LOPOGRAFI DENGAN KLINIS SUSPECT COLON CARCINOMA - Rosy Amelia Azhari; Nanang Sulaksono; Agustina Dwi Prastanti (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT Background :The lopographic examination according to Lampignano and Kendrick (2018) uses barium sulfate contrast media which is inserted through the stoma, using plain photos, AP/PA, Lateral, Oblique, post evacuation. Installation of Radiology Hospital Prof. Dr. Margono Soekarjo Purwokerto using a non-ionic water soluble contrast media mixed with NaCl, inserted into the proximal stoma and anus with plain photos, AP, Lateral. The purpose of the study was to determine the lopographic examination procedure, the reasons for using water soluble contrast media, to find out anatomical information from the AP and Lateral. Methods :This research used qualitative approach with a case study. Data collection were used observation, interviews, documentation. Research respondents were patients, radiographers, radiologist, and dispatching doctors. Data analysis with interactive analysis model. Result : Showed that the lopographic examination was aimed at evaluating the colon after colostomy and chemotherapy. Patients undergo special preparation. The water soluble contrast medium was mixed with NaCl in a ratio of 1: 4 because it was safer than barium sulfate. The reason for insertion of contrast media through the proximal stoma and anus is the absence of a stoma to the distal colon. Anatomical information from the plain photo is the distribution of air in the colon, the AP projection looks contrast to fill the ascending colon, transverse colon, descending colon and superpositioned sigmoid colon. Laterally, the sigmoid colon and rectum are seen. Diagnostic information was not found in colonic carcinoma residif cells.